The Role Price promoting the Tourist Marketing Crisis According to Tourist-Business staff’ Point of View (Case Study about the Tourist Lattakia Hotel) - Nassour, Rizane; Aboud, Hasan (Latakia University Journal - Economic and Legal Sciences Series, 2016)
التسعير السياحي أحد الأنشطة المهمّة في العمل السياحي ،وعنصر مهمّ من عناصر المزيج التسويقي السياحي، لما له من تأثير على الحركة السياحية ، وانطلاقاً من أهمية السعر هدفت هذه الدراسة إلى تسليط الضوء على سياسات السعر الترويجي المتبعة في فندق اللاذقية السياحي خلال فترة الأزمات التسويقية التي تمر بها المنشأة بشكل عام، والأزمة الحالية بشكل خاص، ومعرفة أنواع السياسات الترويجية التي تقوم الإدارة بتطبيقها، ومدى فاعلية كل منها، وقد كانت السياسات المطبقة من قبل إدارة الفندق، هي (التنزيلات، السعر السيكولوجي، سعر الحزمة).كما ركزت الدراسة على بيان مدى تأثر الطلب السياحي على المنتجات المقدمة ، وذلك من خلال تطبيق هذه الاستراتيجية من قبل إدارة الفندق. تكون مجتمع الدراسة من العاملين الإداريين في فندق اللاذقية السياحي في المستويات الإدارية المختلفة ، والبالغ عددهم 35 إدارياً. تم تصميم استبانة وتوزيعها على العاملين الإداريين في فندق اللاذقية السياحي ،كما تم دراسة البيانات وتحليلها باستخدام برنامج spss، وبعد تحليل البيانات توصل الباحث إلى مجموعة من النتائج الآتية: إن سياسة التنزيلات، وسياسة سعر الحزمة المطبقة في المنشاة ناجحة تؤثر بشكل إيجابي على الطلب السياحي، في حين أن سياسة السعر السيكولوجي غير ناجحة ، وتكاد تكون معدومة في المنشأة من وجهة نظر العاملين الإداريين في فندق اللاذقية السياحي. The tourist price is considered one of the important activities of tourist work, and an important element of the tourist marketing mixture elements. This due to its impact on the tourist activity. Because of the importance of Price, this study has aimed to highlight the price promoting policies that Lattakia Hotel followed during marketing crisis phase which the business generally faced, and the current crisis especially; and realizing the promo policies types which the management applied and how effective they were. However, the hotel management’s applied policies have been (discount (reduction), psychological price and package price). Moreover, the study has focused on the extent of the tourist demand impact on the given products through applying this strategy by the Hotel management. The study community consisted of the Lattakia Hotel administrative staff of different administrative levels whose number was 35 members. A questionnaire has been established and distributed to the Lattakia Hotel administrative staff. In addition, data has been studied and analyzed by using SPSS. After data has been analyzed the researcher had a set of results: the discount (reduction) and package price policies applied in the business are successful and have a positive influence on the tourist demand, whereas the psychological price policy is unsuccessful and is almost absent in the business according to Lattakia Hotel Administrative employee.